A Simple Distributed RGC Model of MOSFET for Pre-Pinch Off Region. (1988) - Kumar, Umesh; Mirchandani, Arun
Abstract : The differential equation describing the small signal behavior of a MOSFET channel is derived. Based on the analogy of the channel to distributed transmission lines, which has been very well established in literature, an entirely new RGC line model of MOSFET is presented. The element values of the line are determined by equivalence to a general distributed transmission line and subsequently the model is lumped into a single section in two possible Π and T representations. The postulated model considerably simplifies the study of the properties and behavior of MOSFET structures and can be suitably utilized in analysis and Computer Aided Design.